Optimal Transfers and Participation Decisions in International Environmental Agreements - Carlo Carraro; Johan Eyckmans; Michael Finus (Fondazione Eni Enrico Mattei (FEEM), 2005)
The literature on international environmental agreements has recognized the role transfers play in encouraging participation in international environmental agreements (IEAs), but the few results achieved so far are overly specific and do not exploit the full potential of transfers for successful treaty-making. Therefore, in this paper, we develop a framework that enables us to study the role of transfers in a more systematic way. We propose a design for transfers using both internal and external financial resources and making welfare optimal agreements self-enforcing. To illustrate the relevance of our transfer scheme for actual treaty-making, we use a well-known integrated assessment model of climate change to show how appropriate transfers may be able to induce almost all countries into signing a self-enforcing climate treaty.
Keywords: C72; H23; Q25; Q28; 330; Self-enforcing international environmental agreements; Climate policy; Transfers; Umweltabkommen; Klimaschutz; Internationaler Transfer; Welt